Love or Greatness : Max Weber and Masculine Thinking. - Bologh, Roslyn (Routledge revivals., 2009)
This work, first published in 1990, reissues the first thorough examination of the essentially masculine nature of Max Weber's social and political thinking. Through a detailed examination of his central texts, the author demonstrates Weber's masculine reading of 'social life' and shows how his work advocates a masculine form of life that poses a challenge to contemporary women and to feminism. In particular, she addresses the patriarchal implications of Weber's belief in the need to relegate the ethic of brotherly love to a private sphere in order to make possible rational action and the achi.